TRNSYS Simulation of a Solar Thermal System (SHCS) Integrated into a Building: Case Study of the LPMR Laboratory at the University of Souk Ahras - Brahim BACHA (My University, 2025)
Solar thermal heating and cooling systems integrated into buildings offer a promising renewable energy solution to reduce fossil fuel dependence and mitigate environmental concerns. However, conventional design approaches often neglect the interconnected nature of various parameters, leading to suboptimal system performance. This study investigates the design of two solar heating and cooling systems for an office building (LPMR laboratory) located in Souk Ahras, Algeria (36° 17' 11'' North, 7° 57' 4'' East) with a peak cooling load of 25,000 kJ/h and a peak heating load of 20,000 kJ/h. To enhance this, the study employs the TRNSYS Software to simulate the systems and utilizes two statistical methods: Taguchi's method and the Response Surface Methodology (RSM). These methods allow for a systematic analysis of key parameters influencing the systems' performance, including collector area (A), collector tilt (S), hot water storage tank volume (V), and collector water flow rate (F). The objective is to determine the optimal values of these parameters to improve both the efficiency and cost-effectiveness of the systems. Simulation results indicate that the optimal configuration of the first system involves a Evacuated Tube Collector (ETC) area of 10.46 m², a tilt of 30°, a hot water storage tank volume of 4 m³, and a water flow rate of 780 kg/h. Notably, this configuration achieves an average solar fraction (SF) of 0.76. Regarding the second system, the optimal configuration includes a Flat Plate Collector (FPC) area of 90 m², a tilt of 34°, a hot water storage tank volume of 6.3 m³, and a water flow rate of 615 kg/h. Specifically, this configuration attains an average solar fraction (SF) of 0.63. These results, when compared to previous literature, provide empirical evidence supporting the hypothesis that considering the interrelationship between parameters is crucial for the design of efficient and cost-effective solar heating and cooling systems. These findings contribute valuable insights for a more objective understanding of design considerations in this field. ---------------------------------------------------------------------------------- تقدم أنظمة التبريد والتدفئة التي تشتغل بالطاقة الشمسية الحرارية المدمجة في المباني حلًا واعدًا للطاقة المتجددة لتقليل الاعتماد على الوقود الأحفوري وتخفيف المخاوف البيئية. ومع ذلك، غالبًا ما تهمل مناهج التصميم التقليدية الطبيعة المترابطة لمختلف المتغيرات، مما قد يؤدي إلى أداء غير مثالي للنظام. تستكشف هذه الدراسة تصميم نظامي تبريد وتدفئة شمسييين لمبنى مكتبي (مخبر LPMR) يقع في مدينة سوق أهراس بالجزائر (36° 17' 11'' شمالاً، 7° 57' 4'' شرقاً) مع طلب ذروة تبريد يبلغ 25000 كيلوجول/ساعة وذروة تدفئة تبلغ قيمة 20000 كيلوجول/ساعة . لتعزيز ذلك، تستخدم هذه الدراسة برنامج TRNSYS لمحاكاة النظامين وتوظف طريقتين إحصائيتين: طريقة تاغوتشي ومنهجية سطح الاستجابة (RSM). تسمح هذه الطرق بإجراء تحليل منهجي للمعلمات الرئيسية التي تؤثر على أداء النظامين، بما في ذلك مساحة المجمع (A)، وانحدار المجمع (S)، وحجم خزان الماء الساخن (V)، ومعدل تدفق الماء في المجمع (F). الهدف هو تحديد القيم المثالية لهذه المعلمات لتحسين كل من كفاءة النظامين وفعاليتهما من حيث التكلفة. تشير نتائج المحاكاة إلى أن التكوين الأمثل للنظام الأول يتضمن مساحة مجمع(ETC) تبلغ 10.46 متر مربع، وانحدارًا يبلغ °30 ، وحجم خزان الماء الساخن 4 متر مكعب، ومعدل تدفق للماء يبلغ 780 كجم / ساعة. على وجه الخصوص، يحقق هذا التكوين كسرًا شمسيًا متوسطا (SF) يبلغ 0.76. أما بخصوص النظام الثاني فإن التكوين الأمثل يتضمن مساحة مجمع (FPC) تبلغ 90 متر مربع، وانحدارًا يبلغ 34° ، وحجم خزان الماء الساخن 6.3 متر مكعب، ومعدل تدفق للماء يبلغ 615 كجم / ساعة. على وجه الخصوص، يحقق هذا التكوين كسرًا شمسيًا متوسطا (SF) يبلغ 0.63. توفر هذه النتائج بعد مقارنتها بالأدبيات السابقة أدلة تجريبية تدعم الفرضية القائلة بأن مراعاة الترابط بين المعلمات أمر بالغ الأهمية لتصميم أنظمة التدفئة وتبريد الشمسي الفعالة والمناسبة من حيث التكلفة. تساهم هذه النتائج في رؤى قيمة لفهم أكثر موضوعية لملاحظات التصميم في هذا المجال. ---------------------------------------------------------------------------- Les systèmes de chauffage et de refroidissement solaires thermiques intégrés aux bâtiments offrent une solution d'énergie renouvelable prometteuse pour réduire la dépendance aux combustibles fossiles et atténuer les préoccupations environnementales. Cependant, les approches de conception conventionnelles négligent souvent la nature interconnectée des différents paramètres, conduisant à des performances sous-optimales du système. Cette étude examine la conception de deux systèmes de chauffage et de refroidissement solaires pour un immeuble de bureaux (laboratoire LPMR) situé à Souk Ahras, en Algérie (36° 17' 11'' Nord, 7° 57' 4'' Est) avec une charge de refroidissement de pointe de 25 000 kJ/h et une charge de chauffage de pointe de 20 000 kJ/h. Pour améliorer cela, l'étude utilise le programme TRNSYS pour simuler les systèmes et emploie deux méthodes statistiques : la méthode de Taguchi et la méthodologie des surfaces de réponse (RSM). Ces méthodes permettent une analyse systématique des paramètres clés influençant les performances des systèmes, notamment la surface du collecteur (A), l'inclinaison du collecteur (S), le volume du réservoir d'eau chaude (V) et le débit d'eau du collecteur (F). L'objectif est de déterminer les valeurs optimales de ces paramètres afin d'améliorer à la fois l'efficacité et la rentabilité des systèmes. Les résultats de simulation indiquent que la configuration optimale du premier système implique une surface de collecteur (Collecteur à tubes sous vide ETC) de 10,46 m², une inclinaison de 30°, un volume de réservoir d'eau chaude de 4 m³ et un débit d'eau de 780 kg/h. Notamment, cette configuration atteint une fraction solaire moyenne (SF) de 0.76. En ce qui concerne le deuxième système, la configuration optimale comprend une surface de collecteur (collecteur à plaque plane FPC) de 90 m², une inclinaison de 34 °, un volume de réservoir d'eau chaude de 6,3 m³ et un débit d'eau de 615 kg/h. Spécifiquement, cette configuration atteint une fraction solaire moyenne (SF) de 0.63. Ces résultats, comparés à la littérature précédente, fournissent des preuves empiriques à l'appui de l'hypothèse selon laquelle la prise en compte de l'interrelation entre les paramètres est cruciale pour la conception de systèmes de chauffage et de refroidissement solaires efficaces et rentables. Ces résultats apportent des informations précieuses pour une compréhension plus objective des considérations de conception dans ce domaine.
Keywords: Renewable energy; Solar cooling; Solar heating; Souk Ahras; TRNSYS; Taguchi method; Response Surface Methodology; Optimization.: الطاقة المتجددة ، التبريد الشمسي ، التدفئة الشمسية ، مدينة سوق أهراس ، برنامج ترنزيس ، طريقة تاقوتشي .منهجية سطح الاستجابة .تحسين .; Énergie Renouvelable; Refroidissement Solaire; Chauffage Solaire; Méthode de Taguchi; Méthodologie des Surfaces De Réponse; Optimisation.